The That-Trace Effect—A Surface or a Deep Island Phenomenon? Evidence from Resumption and Prolepsis in Igbo - Mary Amaechi; Doreen Georgi (Languages)
In many languages, a subject/non-subject Ā-extraction asymmetry can be observed: While non-subject extraction is unproblematic, long extraction of the subject requires repair strategies. This phenomenon is known as the that-trace effect. Two broad types of approaches to this effect have been proposed in the literature: (a) structural accounts that prohibit subject extraction in the syntax; (b) surface-oriented PF accounts according to which nothing blocks long subject movement in the syntax, but a surface filter prohibits the output string where a trace follows the complementizer. In this paper, we argue for a syntactic cause of the effect in Igbo (Benue-Congo, Nigeria). The empirical evidence centers around the distribution of resumptive pronouns in the language. We show that Igbo has all the ingredients required for a PF approach to the that-trace effect (viz., long Ā-movement and trace spell-out); nevertheless, it does not apply them to enable long subject extraction but rather resorts to prolepsis (among other strategies). Further evidence against a PF account comes from the impossibility of short subject extraction. Finally, we provide evidence from subextraction from subjects for an antilocality component underlying the subject extraction restriction in Igbo.